Enriching the Study Population for Ischemic Stroke Therapeutic Trials Using a Machine Learning Algorithm - Maharjan, Jenish; Ektefaie, Yasha; Ryan, Logan; Mataraso, Samson; Barnes, Gina; Shokouhi, Sepideh; Green-Saxena, Abigail; Calvert, Jacob; Mao, Qingqing; Das, Ritankar (Frontiers in Neurology, 2022)
Background Strokes represent a leading cause of mortality globally. The evolution of developing new therapies is subject to safety and efficacy testing in clinical trials, which operate in a limited timeframe. To maximize the impact of these trials, patient cohorts for whom ischemic stroke is likely during that designated timeframe should be identified. Machine learning may improve upon existing candidate identification methods in order to maximize the impact of clinical trials for stroke prevention and treatment and improve patient safety. Methods A retrospective study was performed using 41,970 qualifying patient encounters with ischemic stroke from inpatient visits recorded from over 700 inpatient and ambulatory care sites. Patient data were extracted from electronic health records and used to train and test a gradient boosted machine learning algorithm (MLA) to predict the patients’ risk of experiencing ischemic stroke from the period of one day up to one year following the patient encounter. The primary outcome of interest was the occurrence of ischemic stroke. Results After training for optimization, XGBoost obtained a specificity of 0.793, a positive predictive value (PPV) of 0.194, and a negative predictive value (NPV) of 0.985. The MLA further obtained an area under the receiver operating characteristic (AUROC) of 0.88. The Logistic Regression and multilayer perceptron models both achieved AUROCs of 0.862. Among features that significantly impacted the prediction of ischemic stroke were previous stroke history, age, and mean systolic blood pressure. Conclusion MLAs have the potential to more accurately predict the near risk of ischemic stroke within a one-year prediction window for individuals who have been hospitalized. This risk stratification tool can be used to design clinical trials to test stroke prevention treatments in high-risk populations by identifying subjects who would be more likely to benefit from treatment.